Pemahaman Tentang Sayap Dalam Kitab Rut: Studi Kritik Naratif - Rannu Sanderan; Yohanes Krismantyo Susanta (Institut Agama Kristen Negeri Toraja, 2021)
Abstract; This article discusses the meaning of wings according to the book of Ruth in an authentic purpose. By using the narrative methods, in more deeply, this research is intend to examine the basic motive why Ruth uses the word of wings in order to ask Boaz to spread his wings on Ruth. On the other hand, Ruth did not belong to God’s covenant nation. The perspective of the theory of narrative criticism used in this research is to look at the biblical narrative by referring to the analysis of the book of Ruth and its parts of the book as a complete literary work. The aim of this method is focusing on the storyteller or narrator, plot and scene, as well as repetition and keywords, characters, atmosphere, and point of view. The narrative analysis in the results of this paper not based on the author but merely on the text. So that readers can find out the values ​​and theological views conveyed through the text. The result of research on the meaning of wings in this text is Yahweh's own wing (2:12) as a place for Ruth to take refuge. In fact, Ruth was already under God's wing, because she had previously had a strong belief in becoming the covenant people of Yahweh. Hoped that this study can make a theological contribution in studying the God’s sovereignty towards all nations. Abstrak; Artikel ini membahas tentang makna sayap dalam dalam kitab Rut sesuai konteks yang otentik. Dengan metode naratif, riset ini hendak mengkaji secara lebih dalam motif dasariah, mengapa Rut memakai kata sayap dalam rangka meminta kesudian Boas agar mau mengembangkan sayapnya atas Rut. Padahal Rut tidak tergolong bangsa perjanjian Allah. Perspektif teori kritik naratif yang digunakan dalam penelitian ini hendak melihat narasi Alkitab dengan mengacu pada analisa terhadap kitab Rut dan bagian-bagian kitab sebagai sebuah karya sastera yang utuh. Metode ini hendak mengarahkan fokus pada pencerita atau narrator, alur/plot serta adegan, juga pengulangan dan kata kunci, tokoh, suasana, dan sudut pandang. Setelah dikerucutkan lebih tajam, maka analisa naratif dalam hasil tulisan ini bukan pada penggubahnya tetapi ada teks. Sehingga pembaca dapat mengetahui nilai-nilai dan pandangan teologi yang disampaikan melalui teks yang diselidiki. Hasil penelitian tentang makna sayap dalam teks ini adalah sayap Yahweh sendiri (2:12) sebagai tempat bagi Rut untuk berlindung. Sejatinya, Rut sudah berada di bawah sayap Tuhan, karenya ia sebelumnya telah memiliki keyakinan kuat akan masuk menjadi umat perjanjian Yahweh. Diharapkan agar studi kepustakaan ini memberi sumbangsih teologis dalam mengkaji kedaulatan Allah bagi seluruh bangsa.